EMOTIONAL GEOGRAPHY EVIDENCE LEFT FROM PRE-SERVICE TEACHERS’ TEACHING PRACTICE EXPERIENCES DURING THE PANDEMIC - Rayinda Rahmah; Mukhamad Huda; Dewi Puspitasari (Educational Tracker, 2022)
This narrative research exposed four pre-service teachers’ emotions in pre-service teaching practice during the pandemic of Covid-19. It focused on how the pre-service teachers enacted their emotions while they performed various teaching challenges during the pandemic of COVID-19. Written reflections during the pre-service teaching from four pre-service teachers were taken as the data. By employing Andy Hargreaves’ emotional geographies theory, the research indicated that pre-service teachers experienced positive and negative emotions during the practice of teaching.